Climate Action to Unlock the Inclusive Growth Story of the 21st Century - Bhattacharya, Amar.; Ivanyna, Maksym; Oman, William; Stern, Nicholas (Washington, D.C. : International Monetary Fund, 2021)
Climate change is a major threat to the sustainability and inclusiveness of our societies, and to the planet's habitability. A just transition to a low-carbon economy is the only viable way forward. This paper reviews the climate change challenge. It stresses the criticality of systems changes (energy, transport, urban, land use, water) in a climate-challenged world, and the importance of infrastructure investment geared toward such systems changes. The key policies to enable the transition are: public spending on and investment frameworks for sustainable infrastructure, pricing carbon, regulations, promoting sustainable use of natural resources, scaling up and aligning finance with climate objectives, low-carbon industrial and innovation policies, building resilience and adaptation, better measurement of well-being and sustainability, and providing information and education on climate risks. Implemented well, climate action would unlock the inclusive growth story of the 21st century, making our societies more sustainable, inclusive, and prosperous.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; Foreign Exchange; Informal Economy; Natural Disasters and Their Management; Underground Econom